Dangerous snoring detection / Hafiz Ezman Zambri, Hashimah Zahari and Nurhidayu Rosmizi - Zambri, Hafiz Ezman; Zahari, Hashimah; Rosmizi, Nurhidayu (2015)
Snoring is usually a nocturnal sound which without known may disturb and can cause misery by the snorer. Thus, it have developing snorer device that is ‘pillow vibration’ to ease the symptoms of sleep apnea sufferers. It is a pillow that generates vibration by using motor with the universal-vibration motor inside the pillow. The system operates by using a microcontroller Atmega328 that use in Arduino as a main part of the project. The input part of Atmega328 will detect the frequency by using a electric microphone. The audio or signal will amplify by using BC 547 microphone amplifier.BC547 is an NPN bi-polar junction transistor. A transistor, stands for transfer of resistance, is commonly used to amplify current. In addition, the output will connect to the LCD, led, buzzer and motor. The Arduino is multifunction because it can be use in any types of the project. The microcontroller on the board is programmed using the Arduino programming language (based on Wiring) and the Arduino development environment (based on Processing).The features of'pillow is, it is function as an alarm instead of vibrator device. This pillow is comfortable to use with the vibration as well as the firm of the box of the circuit was under cover by the pillow.